Basic models of protection and functioning of the Ukrainian border in modern geopolitical realities: a view from Ukraine - Kotsan, Natalia; Kopachinska, Galina; Vozniuk, Yevheniia; Kotsan, Roman (European Spatial Research and Policy, 2023)
In the article, the authors summarised the concept of state border security. They have suggested a wider interpretation of the border security model. They discussed modern models of border security in a theoretical context. They presented progressive models of security and functioning of Ukraine’s borders and described their features. They emphasised that the modern Ukrainian-Polish boundary represents a partially liberal model of security and functioning and it can be characterised by the operational security model. Different models of the functioning of the Ukrainian-Polish boundary (asymmetrical, selectively simplified, and symmetrical) were identified and connected with the transformational processes of the Ukrainian-Polish relations.